UNATTENDED VS ATTENDED BP MEASUREMENT: MEAN VALUES AND DETERMINANTS OF THE DIFFERENCE. (June 2018) - Paini, A.; Salvetti, M.; Bertacchini, F.; Stassaldi, D.; Maruelli, G.; Arnoldi, C.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: The results of the SPRINT study have called attention on the possible differences between blood pressure (BP) values obtained by health-care professionals in the office, during the visit ("attended BP") as compared to those obtained in the office leaving the patient alone ("automated office BP" or "unattended BP"). Only few studies have compared the two techniques and none of them implemented the approach for unattended BP measurement used in SPRINT by the use of completely automated device for both attended and unattended BP and by the measurement of 3 values after 5 minutes of rest, . Design and method: In 261 consecutive outpatients attending the outpatient clinic at an ESH Excellence Centre, BP values were measured by the physician with an automated oscillometric device (Omron HEM 9000Ai, mean of 3 measurements), after 5 minutes of rest. After the measurement of BP by the physician, the patient was left alone in the room, and the device was programmed to automatically perform 3 BP measurements after 5 minutes. Results: Mean age was 61 ± 16 yrs, 60% F, BMI 26.1 ± 4.2, 88 % with a previous diagnosis of hypertension (64 % treated). Unattended systolic BP (SBP) and diastolic BP (DBP) were both lower as compared to attended SBP (130.1 ± 15.7vs138.6 ± 17.2 mmHg) and DBP (77.1 ± 11.7vs78.9 ± 12.2 mmHg). The differences (Delta) between the values obtained using the two techniques were 8.5 ± 7.9 mmHg for SBP and 1.8 ± 5.6 mmHg for DBP. Delta SBP was directly correlated with age (r = 0.235 p < 0001) and with attended BP values (r = 0.407 p < 0.0001); Delta SBP was significantly lower in males than in females. At multivariate analysis Delta SBP remained independently correlated with age and attended SBP. Delta DBP was directly correlated with attended DBP (r = 0, 322 p < 0.001) and was lower in males. Conclusions: Our findings indicate that "unattended BP" measurement provides values significantly lower as compared to measurements obtained in the presence of the physician. Interestingly, the difference between the values obtained by the two approaches is not constant for all patients, being significantly affected by age, gender and BP values